Review of the Second Five Year Plan West Bengal - Planning Commission (Planning Commission, 1962)
Planning for rapid development of an underdeveloped country like ours is a complicated Jong term process. If we overlook the magnitude of the task it is somewhat comparable to a housing project. In both cases we need a blue print to clearly set out the stages of construction. After that in both cases it involves a long period of construction. the work of construction has to go in stages. In case of the house we build with bricks, in case of the Plan we build with different scheme. In the case of the house we build the foundation first, then the ground floor, then the first floor and so on. the same analogy holds good in respect of planning. Priorities have to be so arranged that what we build first should be able to support what we build afterwards.
West Bengal